Detecting Mesopelagic Organisms Using Biogeochemical‐Argo Floats. Issue 6 (10th March 2020) - Haëntjens, Nils; Della Penna, Alice; Briggs, Nathan; Karp‐Boss, Lee; Gaube, Peter; Claustre, Hervé; Boss, Emmanuel
Abstract: During the North Atlantic Aerosols and Marine Ecosystems Study in the western North Atlantic, float‐based profiles of fluorescent dissolved organic matter and backscattering exhibited distinct spike layers at ∼ 300 m. The locations of the spikes were at depths similar or shallower to where a ship‐based scientific echo sounder identified layers of acoustic backscatter, an Underwater Vision Profiler detected elevated concentration of zooplankton, and mesopelagic fish were sampled by a mesopelagic net tow. The collocation of spike layers in bio‐optical properties with mesopelagic organisms suggests that some can be detected with float‐based bio‐optical sensors. This opens the door to the investigation of such aggregations/layers in observations collected by the global biogeochemical‐Argo array allowing the detection of mesopelagic organisms in remote locations of the open ocean under‐sampled by traditional methods. Plain Language Summary: The largest migration on Earth happens daily when animals migrate to feed on phytoplankton at the surface. They return to the twilight zone at night likely to hide from visual predators. These migrating organisms—zooplankton, fish, squids, and jellyfish—are well studied in some parts of the world's oceans, but their study is limited to the spatial and temporal coverage of ships. At the same time, a network of robots profiling the ocean from the surface to 2, 000 m continuously measures the properties of the water at hundreds of locations daily, but so far, they have not been used for detecting migrating organisms. In this study, we show that migrating organisms can be attracted to emitted light by sensors mounted on the profiling robots and produce anomalous signals that can be used to suggest their presence. This method will help study those animals over extended time scales and in remote areas not easily accessible by ships. In addition, it will improve our interpretation of the profiling robots' measurements. Incorporating recently developed instruments, such as underwater cameras, with existing optical sensors could help study some of those organisms living deep in the ocean's interior. Key Points: We present concurrent observations of mesopelagic organisms with echo sounders, a camera, a net tow, and profiling floats Layers of mesopelagic organisms coincide with distinct spike layers in fluorescence and backscattering profiles Novel application of biogeochemical‐Argo float enables the detection of mesopelagic organisms and their migration